FORMULASI DAN UJI AKTIVITAS SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) SEBAGAI ANTI-HIPERKOLESTEROL DARI KOMBINASI EKSTRAK TEMULAWAK (Curcuma xanthorrhiza Roxb) DAN DAUN SAMBUNG NYAWA (Gynura procumbent (Lour)Merr) MENGGUNAKAN VIRGIN COCONUT OIL SEBAGAI FASE MINYAK - , Aulia Ul Hafizah; , Prof. Dr. Zullies Ikawati, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The previous study has shown that extract combination of C. XanthorrhizaRoxb and G. Procumbens, Lour. Merr. in 75:25 ratio decreased significantly cholesterol blood level in rat. However, due to the extractâs solubilities problem, the extracts were developed in the form of SNEDDS (self-nanoemulsifying drug delivery system). The purposes of this study were to formulate the extracts combination in form of SNEDD using virgin coconut oil as the oil phase and to evaluate the cholesterol lowering activity of the optimum formula obtained. The emulsification time, extract loading, and anti-cholesterol activity test were used as parameters for determining of the SNEDDS optimum formula for Curcuma xanthorrhiza Roxb and GynuraProcumbens (lour) Merr extracts combination. The anti-cholesterol activity test was carried out using four male Wistar rats which were that randomly selected. Blood cholesterol levels were checked on day 0, 30, 60, 67, 70. The ANOVA statistical analysis were used to determine the difference between the data blood cholesterol level. The results showed that the optimum formula, i. e